New Opportunities for Complex Therapy in Patients with Dry Eye Syndrome of Various Etiologies - V. V. Brzheskiy; S. Yu. Golubev; O. I. Lebedev; E. S. Milyudin; A. S. Apostolova; A. V. Surov; E. L. Efimova; E. V. Varlashina; I. N. Gorbachevskaya; V. O. Kirichenko (Oftalʹmologiâ, 2020)
The purpose: to evaluate the effectiveness of the Delfanto® in the complex therapy of patients with dry eye syndrome of various etiologies and severity of the clinical course.Patients and methods. 114 patients (228 eyes) with dry eye syndrome of various etiologies were examined: 72 patients with chronic meibomian blepharitis and dysfunction of the meibomian glands (xerosis due to increased evaporation of the tear film), 33 women with perimenopause (a mixed form of xerosis with a predominant decrease in the production of components of the tear film) and 9 persons with Syegren syndrome (xerosis due to a pronounced decrease in tear production). All patients received individually selected tear replacement therapy over the past weeks and the drug was not replaced throughout the study. At the same time, patients with mild and moderate clinical course of SSG for 30 days received Delfanto® at a dosage of 60 mg, and with severe course — 120 mg per day.Results. All patients on the background of complex therapy showed a significant decrease in the severity of subjective manifestations of the dry eye syndrome, an increase in the of the tear film stability and indicators of tear production. At the same time, the dynamics of changes in these parameters of the course of the xerotic process increased as the therapy continued, reaching a maximum by the 30th day. The maximum effect of Delfanto® in the complex therapy of patients with dry eye syndrome was observed in patients with chronic meibomian blepharitis. Moreover, patients with a mild clinical course of cornealconjunctival xerosis were the most susceptible to the therapy.Conclusion. The effectiveness of the complex therapy for patients with dry eye syndrome can be significantly increased by prescribing Delfanto® in a daily dose of 60 mg for mild and moderate xerosis and 120 mg — for severe disease. Delfante® can be recommended for widespread clinical use in complex treatment of patients with various clinical and pathogenetic forms of dry eye syndrome.